Together We Stand? Agglomeration in Indian Manufacturing - Fernandes, Ana M.; Sharma, Gunjan (World Bank, Washington, DC, 2012)
This paper uses plant-level data to examine the impact of industrial and trade policy reforms on the geographic concentration of manufacturing industries in India from 1980 to 1999. First, the research shows that de-licensing and liberalization in foreign direct investment significantly reduced spatial concentration, but trade reforms had no significant effect on spatial concentration. Second, plants respond differently to policy reforms based on their size. Liberalization in foreign direct investment and de-licensing caused small plants to disperse, while trade liberalization had the opposite effect. However, for large plants trade liberalization led to lower spatial concentration.